The Rhetorical State of Alert before the Iraq War 2003 - Mral Brigitte (Nordicom Review, 2006)
Initiating an attack on another country is always a questionable venture, whether one chooses to call it war or prefers euphemisms such as conflict, incident, action or peacecreating measures. This study examines how the arguments were developed prior to the military actions in Iraq 2003. The events have been presented in vague and often distorted value terms and metaphors where war becomes peace, attacks becomes ‘pre-emptive defence’, military invasion becomes ‘change of regime’, occupation becomes ‘humanitarian intervention’.This study provides a diachronic survey of the chain of events from rhetorical perspectives, as well as a synchronic analysis of recurring rhetorical themes - especially of vague concepts and metaphors.